Political Questions Judicial Answers : Does the Rule of Law Apply to Foreign Affairs?. - Franck, Thomas M. (Princeton University Press, 2012)
Almost since the beginning of the republic, America's rigorous separation of powers among Executive, Legislative, and Judicial Branches has been umpired by the federal judiciary. It may seem surprising, then, that many otherwise ordinary cases are not decided in court even when they include allegations that the President, or Congress, has violated a law or the Constitution itself. Most of these orphan cases are shunned by the judiciary simply because they have foreign policy aspects. In refusing to address the issues involved, judges indicate that judicial review, like politics, should stop at the water's edge--and foreign policy managers find it convenient to agree! Thomas Franck, however, maintains that when courts invoke the "political question" doctrine to justify such reticence, they evade a constitutional duty. In his view, whether the government has acted constitutionally in sending men and women to die in foreign battles is just as appropriate an issue for a court to decide as whether property has been taken without due process. In this revisionist work, Franck proposes ways to subject the conduct of foreign policy to the rule of law without compromising either judicial integrity or the national interest. By examining the historical origins of the separation of powers in the American constitutional tradition, with comparative reference to the practices of judiciaries in other federal systems, he broadens and enriches discussions of an important national issue that has particular significance for critical debate about the "imperial presidency."